2014
DOI: 10.1038/nri3705
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune activation in neurodegenerative disease

Abstract: The triggering of innate immune mechanisms is emerging as a crucial component of major neurodegenerative diseases. Microglia and other cell types in the brain can be activated in response to misfolded proteins or aberrantly localized nucleic acids. This diverts microglia from their physiological and beneficial functions, and leads to their sustained release of pro-inflammatory mediators. In this Review, we discuss how the activation of innate immune signalling pathways - in particular, the NOD-, LRR- and pyrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
916
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,164 publications
(946 citation statements)
references
References 167 publications
20
916
0
10
Order By: Relevance
“…There are also increases in interleukin-1, interleukin-6 and tumor necrosis factor (TNF) in schizophrenia (Potvin et al 2008), and in AD (Heneka et al 2014), indicating neuroinflammation and decreased hippocampal volume in both diseases (Mondelli et al 2011), (Voevodskaya et al 2014). Therefore, despite being different diseases, AD and schizophrenia are linked; however, there is some disagreement as to how close this link actually is.…”
Section: Schizophrenia and Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…There are also increases in interleukin-1, interleukin-6 and tumor necrosis factor (TNF) in schizophrenia (Potvin et al 2008), and in AD (Heneka et al 2014), indicating neuroinflammation and decreased hippocampal volume in both diseases (Mondelli et al 2011), (Voevodskaya et al 2014). Therefore, despite being different diseases, AD and schizophrenia are linked; however, there is some disagreement as to how close this link actually is.…”
Section: Schizophrenia and Alzheimer's Diseasementioning
confidence: 99%
“…Bipolar disorder and dementia may share common etiological factors, such as oxidative stress and reduced neurotrophic factors that are both key mediators in the pathophysiology of mood disorders (Bauer et al 2014) and AD (Heneka et al 2014), as well as neuroinflammation (Stich et al 2014), which occurs in both comorbidities, with increases shown in pro-inflammatory interleukin, tumor necrosis factor alpha (TNF-α) and arachidonic acid cascade enzymes in the postmortem brains taken from BD and AD patients .…”
Section: Bipolar Disorder and Alzheimer's Diseasementioning
confidence: 99%
“…Depuis, NLRP3 a été impliqué dans de nombreuses pathologies multifactorielles à composante inflammatoire, dont l'arthrite goutteuse, l'athérosclérose, le diabète de type 2 et la stéatose hépatique non-alcoolique [6,7]. Il est également impliqué dans plusieurs maladies neurodégénéra-tives, dont la sclérose en plaques et les maladies d'Alzheimer et de Parkinson, ainsi que dans les pathologies associées au vieillissement [6][7][8][9]. NLRP3 est aussi important au cours des infections par diffé-rents pathogènes.…”
unclassified
“…Although the etiologic mechanisms of AD are poorly understood, more recently, an analysis of human brain AD samples has shown highly expressed inflammatory cytokines and an up-regulation in inflammatory genes during the early stages of AD (Hollingworth et al, 2011;Sudduth et al, 2013). During neurodegenerative disease development, microglia and other cell types, including cytokines, are activated in response to misfolded proteins in the brain, also participate in the active immune defense, and are particularly important in regulating tissue homeostasis and in preserving the structural and functional characteristics of the brain (Heneka et al, 2014;Fakhoury, 2015). McGeer et al (1988) demonstrated the activation of microglial cells and astroglial cells in close proximity to the damaged or dying neurons.…”
Section: Inhibition Of Chronic Inflammation In Ad By Geniposidementioning
confidence: 99%